GAMBARAN PENGELOLAAN DOKUMEN REKAM MEDIS DI PUSKESMAS CIPONDOH KOTA TANGERANG - Muhammad Yasin,; Irda Sari, (Journal of Innovation Research and Knowledge, 2021)
Medical records are one of the units in the puskesmas whose existence is quite important. Medical records contain records of patient data that are of legal value and can affect the quality of health services. Management of medical record documents to achieve the establishment of administrative order and health services in Cipondoh Health Center, Tangerang City. The management of medical record documents is needed as one of the health care facilities. Cipondoh Health Center tangerang city has 5 medical records officers. Medical records officers who have a background in medical records are only 1 person. Officers at TPP (Patient Registration Center) sometimes do not convey the rights and obligations of patients, where the information is important to the patient. The purpose of this study is to describe the management of medical record documents in cipondoh health center in order to create an orderly admnistrasi and health services. The result of this study is that the management system of medical record documents has been conducted sequentially and systematically. However, there are some things in the management of medical records that are not in accordance with the operational standards of puskesmas procedures, regulations, and theories. The medical records officer does not yet have a clear description of the task so concurrently the task. The design of the form is in accordance with the theory. There are incomplete medical records such as filling out diagnoses, diagnostic codes, and doctor's initials. the purpose of the researchers here to describe the management of medical record documents in cipondoh health center Tangerang City. The advice that can be given is in coding the diagnosis of the disease, it should be done by opening the ICD-10 book so that the patient's diagnostic code becomes accurate